2021
DOI: 10.1088/1755-1315/880/1/012056
|View full text |Cite
|
Sign up to set email alerts
|

The adverse effect of long term intake of Monosodium Glutamate on kidney performance

Abstract: Monosodium glutamate (MSG) is a food additive that is considered as a water and environmental pollutant and affects the tissues of the living being. This study was aimed to find the effect of long-term administration of MSG on the mass of mesangial cells of the kidneys. Forty adult male rats were divided into four groups (10 each). Control groups 1&2 were supplied orally with distilled water for 30 and 60 days, respectively. Treatment groups 1&2 were supplied orally with 15 mg/kg Bwt of MSG for 30 &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The kidney in sulfite group appeared with slight congestion of the interstitial blood vessels and necrobiosis of renal tubular epithelium. Similar findings were observed by Hamad and Hamed, (2020); Hussin et al (2021). In similar study, MSG treated animals revealed prominent areas of severe vacuolated hepatocyte with pyknotic nuclei, marked dilated central vein congested with hemolysis blood cells and perivascular inflammatory cells infiltrations.…”
Section: Discussionsupporting
confidence: 88%
“…The kidney in sulfite group appeared with slight congestion of the interstitial blood vessels and necrobiosis of renal tubular epithelium. Similar findings were observed by Hamad and Hamed, (2020); Hussin et al (2021). In similar study, MSG treated animals revealed prominent areas of severe vacuolated hepatocyte with pyknotic nuclei, marked dilated central vein congested with hemolysis blood cells and perivascular inflammatory cells infiltrations.…”
Section: Discussionsupporting
confidence: 88%
“…However, group 4 is distinguished, having the highest levels, with statistical differences compared to the Control group. Other experimental studies on adult rats support the idea that higher values of CR appear in the experimental group, compared to the Control one, when the following doses of MSG are administered as 3 g/kg bw/day for six months [83], and 15 mg/kg bw/day for 30 and 60 days, respectively (increased values depending on the period of administration) [27]. Also, the study by Al-Deri A.…”
Section: Urea (Ur) and Creatinine (Cr)mentioning
confidence: 70%
“…The potential toxicity of MSG has been evaluated mainly through preclinical studies. The reported side effects of MSG included (but were not limited to) hepatotoxicity, nephrotoxicity, reproductive system toxicity, cardiotoxicity, neurotoxicity [25][26][27][28][29][30][31]. It has been demonstrated that administration of MSG resulted in histological alterations and impairment in biochemical and metabolic markers such as aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, total or direct bilirubin [32,33], cholesterol, triglycerides, creatinine [34] and urea [35].…”
Section: Positive and Negative Aspects Of The Biological Behaviour Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, rats exposed to 3 g/kg bw of MSG for 6 months had significantly higher serum levels of malondialdehyde(MDA), blood urea nitrogen(BUN), creatinine, uric acid, and Caspase-9, NGAL, and KIM-1 [40]. In addition, rats exposed to 15 mg/kg bw of MSG for 30 and 60 days developed mesangial proliferative glomerulonephritis due to an expansion in a mesangial mass characterised by mesangial cell hypertrophy and hyperplasia [41]. According to a study rats given MSG at a variety of doses for 30 days had higher urea-creatinine blood concentrations [42].…”
Section: Effect On Renal Toxicitymentioning
confidence: 99%